Flax seed an amazing medicinal plant - Yadav, Rashmi; Kaur, Vikender; Rana, J C; Singh, Anil K; Tripathi, Kuldeep (Indian Farming, 2018)
Flax being a bearer of so many amazing medicinal properties, we should include the linseed or flax in our daily diet. It can be utilized in ground form and added in cakes, cookies or breads. You can use them as sprouts or roasted form. Powder of roasted linseed can also sprinkle on salad, vegetables and soup gives a different taste to the food.